Assessment of the micro-tensile strength of the composites for the various antioxidants: An In Vitro study - Vishwaja Uppalapati; Jasmine M Antony; Pratibha Singh; Tom P Varghese; Smita D Dutta; K Shashank; Mohammed Mustafa (Wolters Kluwer Medknow Publications, 2024)
Introduction: The application of the antioxidants after the teeth are bleached has been advocated to fasten the restorative process post-bleaching. The motive of this study was to examine and assess the micro-tensile binding strength of bleached enamel to the resin using a variety of antioxidant solutions. Finding the reason for the tooth fracture was the secondary outcome measured. Materials and Methods: An in vitro study was planned with 100 human extracted teeth, with 20 in each group with one as controls and 4 others tested for the antioxidants sodium ascorbate, epigallocatechin gallate, chitosan, and proanthocyanidin application. The bond strength of bleached enamel to the resin was well as the failure type was assessed after the values were noted and compared using the ANOVA and Tukey's methods keeping P < 0.05 as significant. Results: Epigallocatechin gallate specimens displayed the maximum micro-tensile bond strength under the investigational circumstances, whereas controls displayed the lowest micro-tensile bond strength. There was statistical alteration in micro-tensile bond strengths between all the groups except between epigallocatechin gallate vs chitosan and sodium ascorbate vs proanthocyanidin. High statistical significance was seen between the control and the antioxidant groups as well as between sodium ascorbate and epigallocatechin gallate and chitosan. Conclusion: The antioxidant chemicals significantly augmented the bond strength of bleached enamel to the resin that had been bleached. Also, when compared to the other experimental groups, epigallocatechin gallate and chitosan treatment displayed the greatest mean bond strength values.